Igneous Rock Associations 27. Chalcophile and Platinum Group Elements in the Columbia River Basalt Group: A Model for Flood Basalt Lavas - Reidel, Stephen P.; Barnett, D. Brent (Geoscience Canada, 2020)
The Columbia River Basalt Group is the youngest and best preserved continental Large Igneous Province on Earth. The 210,000 km3 of basaltic lavas were erupted between 16.6 and 5 Ma in the Pacific Northwest, USA. The peak of the eruptions occurred over a 700,000-year period when nearly 99% of the basalts consisting of the Steens, Imnaha, Picture Gorge, Grande Ronde and Wanapum Basalts were emplaced. In this study we examined the Platinum Group Elements (PGEs) Pt and Pd, and the chalcophile elements Cu and Zn in the Columbia River Basalt Group. The presence of Pt, Pd and Cu in the compositionally primitive Lower Steens, Imnaha and Picture Gorge Basalts suggests that the Columbia River Basalt Group magma was a fertile source for these elements. The PGEs are contained mainly in sulphides in the earliest formations based on their correlation with immiscible sulphides, sulphide minerals and chalcophile elements. Grande Ronde, Wanapum and Saddle Mountains Basalts are depleted in PGEs and chalcophile elements compared to earlier formations. Sulphur was saturated in many flows and much of it probably came from assimilation of cratonic rock from a thinned lithosphere. We propose a model where the presence or absence of PGEs and chalcophile elements results primarily from the interaction between an advancing plume head and the crust/lithosphere that it encountered. The early lavas erupted from a plume that had little interaction with the crust/lithosphere and were fertile. However, as the plume head advanced northward, it assimilated crustal/lithospheric material and PGE and chalcophile elements were depleted from the magma. What little PGE and chalcophile elements remained in the compositionally evolved and depleted Grande Ronde Basalt flows mainly were controlled by substitution in basalt minerals and not available for inclusion in sulphides.